PENGARUH TENAGA KERJA, MODAL, DAN JARAK TEMPUH MELAUT TERHADAP PENDAPATAN NELAYAN DI KELURAHAN PANGALI-ALI KECAMATAN BANGGAE KABUPATEN MAJENE - Reni Ruswanty; Muhammad Siri Dangnga; Andi Sitti Halimah (Jurnal Pendidikan Teknologi Pertanian, 2022)
This study aimed to determine the effect of labor, capital, and mileage at sea the income of fishermen in the village of Pangali-Ali District of Banggae Majene. Data collected by direct observation, interviews and documentation. The results of the study concluded that the capital variables and mileage at sea have a significant impact on fishermen's income, which means that any capital increase and additional of mileage at sea, then there is an increase in the income of fishermen. which means that any capital increase and additional mileage at sea, then there is an increase in the income of fishermen. While the variable labor has no effect on the income of fishermen fishing in the Village Pangali-Ali District of Banggae Majene.